The burden of diarrhea, etiologies, and risk factors in India from 1990 to 2019: evidence from the global burden of disease study - Deepak Kumar Behera; Sanghamitra Mishra (BMC, 2022)
Abstract Background This study aims to measure the burden of diarrhea in India and analyze the trend of mortality associated with it for the past 30 years. We also intend to find the prevailing etiology and risk factors associated with diarrheal mortality in India. Methods The study has used the latest round of Global Burden of Disease (GBD) study-2019. GBD data is available across age groups and gender-wise over the period from 1990 to 2019. The study has identified 13 etiologies for the cause of diarrhea deaths and 20 risk factors to analyze the burden of disease. Results Our study shows, childhood diarrhea has declined over the years significantly, yet contributes to a larger share of DALYs associated with the disease. Among all the death cases of Diarrhea, in 2019, the most prevalent disease-causing pathogen is found to be Campylobacter. But Adenovirus is the major contributor to childhood diarrheal deaths. Though the burden of diarrhea is declining over the period, still there is a need to progress the interventions to prevent and control diarrhea rapidly to avoid the huge number of deaths and disabilities experienced in India. Conclusions Consumption of safe and clean water, proper sanitation facility in every household, required nutrition intake by mother and child, safe breastfeeding and stool disposal practices and careful case management, rotavirus vaccination are some of the effective interventions to be implemented all over the country. Further, evidence-based policies should be made and implemented to sustain diarrhea prevention programs.